Implication of Zoning Regulation on Environmental Protection and Land Rights After Enactment of Job Creation Law - Luh Putu Yeyen Karista Putri (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2023)
Job Creation Law, which was re-enacted in 2023, amended 78 Acts in Indonesia simultaneously, including the Spatial Planning Act. The law requires all local authorities to enact detailed plan (RDTR) supplemented with zoning regulation. The statutory approach is used to analyze available options to harness zoning regulation as an instrument for environmental protection. A case study on RDTR and zoning regulation of the South Kuta sub-district was conducted to examine the impact of RDTR on the land right and outline constraints that may hamper RDTR drafting and implementation. The results show that zoning regulation can be an ultimate tool for environmental protection, provided several conditions are met. First, local authorities must reserve existing forests and, even better, allocate additional green areas. Secondly, the central government must provide a comprehensive manual, advise and supervise local authorities to ensure favorable zoning regulations for the environment. On the other hand, zoning regulations must be updated to accommodate development needs and support the small-scale business by providing alternatives for mixed-land use. Local authorities must consider the area's characteristics, including economic and socio-cultural factors, and apply objective (science-based criteria) to determine the zoning while improving staff expertise, outsourcing professional advice, and allowing public participation. It is critical to oversee the zoning-making process all over Indonesia because once enacted; it will be applicable for 20 years under rigorous requirements for alteration.